MODERN LABORATORY METHODS OF DIAGNOSING SEPSIS - Bozorova Sevara Yusuf kizi,; Rustamova Rahbarkhon Botir kizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Sepsis is a complex clinical and pathophysiological syndrome that occurs due to a dysregulated systemic response of the body to an infectious process and is accompanied by the development of organ dysfunction. In modern conditions, laboratory diagnosis of sepsis is considered one of the key components for early disease detection, risk stratification, prognostic assessment, and monitoring of therapy effectiveness [22,23,24].